2021
DOI: 10.1007/s00421-021-04741-1
|View full text |Cite
|
Sign up to set email alerts
|

Relating cardiorespiratory responses to work rate during incremental ramp exercise on treadmill in children and adolescents: sex and age differences

Abstract: Purpose Evaluation of cardiopulmonary exercise testing (CPET) slopes such as $$d\mathrm{H}\mathrm{R}/d{\mathrm{W}\mathrm{R}}_{\mathrm{t}\mathrm{o}\mathrm{t}}$$ d H R / d W R t o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…For example, Reybrouck et al 15 reported the V̇O 2max in boys aged 9–16 in the range of 50.6–56.6 mL O 2 min −1 kg −1 and in girls at the same age between 42.2 and 43.7 mL O 2 min −1 kg −1 . Similar values of V̇O 2max for the same age groups of children were recently reported by Lai et al 14 . These findings show that the values of V̇O 2max in children, expressed in relative values, are on a level similar to or even higher than healthy adults 22 – 24 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For example, Reybrouck et al 15 reported the V̇O 2max in boys aged 9–16 in the range of 50.6–56.6 mL O 2 min −1 kg −1 and in girls at the same age between 42.2 and 43.7 mL O 2 min −1 kg −1 . Similar values of V̇O 2max for the same age groups of children were recently reported by Lai et al 14 . These findings show that the values of V̇O 2max in children, expressed in relative values, are on a level similar to or even higher than healthy adults 22 – 24 .…”
Section: Discussionsupporting
confidence: 90%
“… Value calculated based on the data collected in a paper by Lai et al 14 (for comparisons, see also Reybrouck et al 15 ). …”
Section: Discussionmentioning
confidence: 99%
“…In general, exercise capacity increases during physical growth and reaches its peak in early adulthood. 24,25 Therefore, this growth may lead to confusion in the interpretation of exercise capacity. In previous studies, a cardiopulmonary exercise test (CPET) was used in the assessment of exercise capacity and longer-term follow-up was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the interpretation of CPET poses an additional challenge related to physical changes during growth [11]. In general, exercise capacity increases with growth to reach a maximum in early adulthood [12][13][14][15]. To avert confounding, there is a need to relate CPET parameters with metrics of growth.…”
Section: Introductionmentioning
confidence: 99%